Protective Mechanism of Fagopyrum esculentum Moench. Bee Pollen EtOH Extract Against Type II Diabetes in a High-Fat Diet/Streptozocin-Induced C57BL/6J Mice - Zhang, Jinjin; Cao, Wei; Zhao, Haoan; Guo, Sen; Wang, Qian; Cheng, Ni; Bai, Naisheng (Frontiers in Nutrition, 2022)
Bee pollen is known as a natural nutrient storehouse and plays a key role in many biological processes. Based on the preliminary separation, identification, and characterization of the main active components of F. esculentum bee pollen (FBP), the protective effects of F. esculentum bee pollen extract (FBPE) on high-fat-diet and streptozocin (STZ) induced type II diabetes mellitus (T2DM) was evaluated in this study. The results revealed that FBPE contains 10 active compounds mainly including luteolin (9.46 g/kg), resveratrol (5.25 g/kg), kaemferol (3.67 g/kg), etc. The animal experiment results showed that FBPE could improve HFD-STZ induced T2DM mice. Moreover, the underlying mechanism of the above results could be: i)FBPE could reduce the inflammation related to PI3K/Akt singling pathway, and ii) the gut microbiota remodeling. The results of correlation analysis showed Candidatus Arthromitus and SMB53 indicated positive correlations to TNF-α; Coprococcus, Ruminocossus, and Odoribacteraceae reported negative correlations to TGF-β. That FBPE has an outstanding ability to improve T2DM and could be used as a kind of potential functional food for the prevention of T2DM.